AB0546 IS IMMUNOLOGICAL PROFILE THE PRIMARY DRIVING FORCE BEHIND CLINICAL PICTURE OF SJÖGREN SYNDROME?. (June 2019) - Perdan-Pirkmajer, Katja; Hocevar, Alojzija; Rotar, Ziga; Tomsic, Matija; Gaspersic, Natasa; Praprotnik, Sonja
Abstract : Background: Primary SS (pSS) is a unique autoimmune disorder with a diverse spectrum of clinical and serological manifestations. Multiple clinical and laboratory determinants have been suggested to affect disease progression. Among these, early-onset (up to 35 years) has been proposed to indicate more severe disease 1 . Objectives: To determine possible clinical and laboratory differences between pSS patients diagnosed at 35 years or younger and those diagnosed after the age of 35. Methods: We analyzed a single-centre cohort of 228 adult patients with pSS. For 189 consecutive patients diagnosed between the years 2002 and 2008, the data were collected retrospectively from medical charts, while 39 consecutive patients diagnosed from 2016 to 2018 were followed prospectively. Clinical and laboratory data at diagnosis were collected as defined by ESSDAI. The patients were monitored for new organ involvement during the follow-up period. Categorical variables were compared between those diagnosed ≤ 35 years and after 35 years using the χ 2 -test or Fisher's exact test. Continuous variables were compared using the Mann-Whitney U test. A multivariate logistic regression model was used to test the association between early- and over 35 years-onset pSS, anti-SSA positivity, baseline ESSDAI, the duration of follow-up period and the progression of pSS defined as new organ involvement during the follow-up period. Results: All patients in our cohort fulfilled the 2002 classification criteria 2 . There were 24 (87.5% female, median age 32.5 (IQR 29-34)) early-onset patients and 204 (92.9% female, median age 59 (IQR 51-67)) patients diagnosed after the age of 35. The patients were monitored for new organ involvement during the follow-up period ((6.5 (IQR 3-13) years in the early-onset group and 5 (IQR 2-10) years in the > 35 years group). The early-onset group presented with a significantly higher frequency of salivary gland enlargement (25.0% vs 7.8%, p = 0.017), cutaneous involvement (25.0% vs 5.9%, p = 0.006) cryoglobulinaemia (37.5% vs 12.3%, p<0.004), RF positivity (50% vs 25.5%, p <0.028), anti-SSA positivity (87.5% vs 51.5% (p<0.001) and anti-SSb positivity (50% vs 22.8% (p<0.004). The presence of anti-SSA (odds ratio (OR) 3.93, 95% CI 1.69–9.12, p=0.001), and longer period of follow-up (OR 1.16, 95% CI 1.09–1.25, p<0.001), but not early onset of pSS (OR 0.68, 95% CI 0.24–1.88, p=0.452), were independently associated with new organ involvement during the follow-up. There was a tendency for an association of higher ESSDAI at baseline with adverse outcome (OR 1.06, 95% CI 0.99–1.12, p=0.075). Conclusion: Data from our cohort suggest that more aggressive disease course was associated with the presence of anti-SAA regardless of the age of pSS onset. References: [1] Anquentil C, et al. Rheumatology (Oxford). 2018 doi:10.1093/rheumatology/key392. [2] Vitali C, et al. Ann Rheum Dis 2002;61:554–8. Disclosure of Interests: None declared